Pemanfaatan Media Powtoon Sebagai Sarana Meningkatkan Motivasi Belajar dalam Pembelajaran Teks Narasi pada Peserta Didik Kelas X SMK Negeri 1 Bokat - Oktaviyanti Oktaviyanti; Supriyadi Supriyadi; Nuramila Nuramila (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to describe the use of Powtoon media in increasing student learning motivation in narrative text learning. The location of this research took place on grade X students of SMK Negeri 1 Bokat in the 2024/2025 Academic Year. Data were obtained through observation, questionnaires, and documentation, then analyzed descriptively qualitatively. The results of the study indicate that the use of Powtoon media can be applied as a means to significantly increase student learning motivation. Attractive visual displays, dynamic animations, and audio support make the learning process more interactive, fun, and easy to understand. Students appear more focused, active, and enthusiastic in participating in learning activities. Before the use of Powtoon, learning narrative text tended to be monotonous and less interesting. However, after the application of this media, students showed increased interest, involvement, and understanding of the material. Thus, the use of Powtoon can be an alternative learning media that is effective in increasing student learning motivation in learning narrative text.